Odpowiedzi

2009-12-14T19:10:42+01:00
-2x+y=12 I *3
3x-3y=1

-6x +3y = 36
3x-3y=1
___________+
-3x=37 I : (-3)
x= -11¹/₃
3*(-11¹/₃ ) - 3y = 1
-37-3y=1 I +37
-3y= 38 I :(-3)
y = - 11 ⅔
x= -11¹/₃
Najlepsza Odpowiedź!
2009-12-14T19:11:34+01:00
-2x+y=12 / * 3
3x-3y=1

-6x+3y=36
3x-3y=1

-3x = 37 / : (-3)
x = 37/3 = 12 i jedna trzecia

3x-3y=1
3 * 37/3 - 3y = 1
-3y = 37 / : (-3)
y= - 12 i jedna trzecia

2009-12-14T19:14:02+01:00

-2x+y=12
3x-3y=1

y = 12 + 2x
3x - 36 - 6y = 1

y = 12 + 2x
-3y = 37

y = 12 + 2x
x = 12 ¹/₃

y = 12 + 24 ⅔
x = 12 ¹/₃

y = 36 ⅔
x = 12 ¹/₃

y =